The out-of-pocket burden of chronic diseases: the cases of Belgian, Czech and German older adults - Kočiš Krůtilová, Veronika; Bahnsen, Lewe; De Graeve, Diana (BMC health services research, 2021)
BACKGROUND: Out-of-pocket payments have a diverse impact on the burden of those with a higher morbidity or the chronically ill. As the prevalence of chronic diseases increases with age, older adults are a vulnerable group. The paper aims to evaluate the impact of chronic diseases on the out-of-pocket payments burden of the 50+ populations in Belgium, the Czech Republic and Germany. METHODS: Data from the sixth wave of the Survey of Health, Ageing and Retirement in Europe is used. A two-part model with a logit model in the first part and a generalised linear model in the second part is applied. RESULTS: The diseases increasing the burden in the observed countries are heart attacks, high blood pressure, cancer, emotional disorders, rheumatoid arthritis and osteoarthritis. Reflecting country differences Parkinson's disease and its drug burden is relevant in Belgium, the drugs burden related to heart attack and outpatient care burden to chronic kidney disease in the Czech Republic and the outpatient care burden of cancer and chronic lung disease in Germany. In addition, we confirm the regressive character of out-of-pocket payments. CONCLUSIONS: We conclude that the burden is not equitably distributed among older adults with chronic diseases. Identification of chronic diseases with a high burden can serve as a supplementary protective feature.
Keywords: senioři; chronická nemoc; Belgium; Evropa; Older adults; Humans; Belgie; Německo; Chronic diseases; Aged; Czech Republic; Out-of-pocket burden; Germany; Europe; lidé; Chronic Disease; Česká republika